A Functional Magnetic Resonance Imaging Study of Spatial Working Memory in Children with Prenatal Alcohol Exposure: Contribution of Familial History of Alcohol Use Disorders. (16th October 2012) - Norman, Andria L.; O'Brien, Jessica W.; Spadoni, Andrea D.; Tapert, Susan F.; Jones, Kenneth Lyons; Riley, Edward P.; Mattson, Sarah N.
Abstract : Background: Heavy prenatal alcohol exposure leads to widespread cognitive deficits, including problems with spatial working memory (SWM). Neuroimaging studies report structural and functional abnormalities in fetal alcohol spectrum disorders (FASD), but interpretations may be complicated by the co‐occurrence of a family history of alcoholism. Since this history is also linked to cognitive deficits and brain abnormalities, it is difficult to determine the extent to which deficits are unique to prenatal alcohol exposure. Methods: Age‐matched subjects selected from 2 neuroimaging studies underwent functional imaging while engaging in a task assessing memory for spatial locations relative to a vigilance condition assessing attention. Pairwise comparisons were made for the following 3 groups: children with histories of heavy prenatal alcohol exposure (ALC, n  = 18); those with no prenatal alcohol exposure, but a confirmed family history of alcoholism (FHP, n  = 18); and nonexposed, family history negative controls (CON, n  = 17). Results: Relative to CON and FHP, the ALC group showed increased blood oxygen level dependent (BOLD) response in the left middle and superior frontal gyri for the SWM condition relative to the vigilance condition (SWM contrast). Additionally, the ALC group showed unique BOLD response increases in the left lingual gyrus and right middle frontal gyrus relative to CON, and left cuneus and precuneus relative to FHP. Both ALC and FHP showed greater activation compared to CON in the lentiform nucleus and insular region. Conclusions: These results confirm previous studies suggesting SWM deficits in FASD. Differences between the ALC group and the CON and FHP groups suggest the left middle and superior frontal region may be specifically affected in alcohol‐exposed children. Conversely, differences from the CON group in the lentiform nucleus and insular region for the ALC and FHP groups may indicate this region is associated with family history of alcoholism rather than specifically with prenatal alcohol exposure.